The Influence of the 9E Learning Cycle with A STEM Approach on Students' Science Process Skills in Static Fluid Topics - M Ali Alfian; Parno Parno; Hari Wisodo; Noorzana Khamis (Jurnal Penelitian Pendidikan IPA, 2024)
This study investigated the effectiveness of integrating the 9E Learning Cycle Model with STEM approaches to enhance students' Science Process Skills (SPS) in static fluid concepts. The research employed a mixed-methods embedded experimental design with 32 senior high school students. Quantitative data were collected through pre- and post-tests, while qualitative data were gathered via observations and interviews. Results showed significant improvements across all SPS components, with N-gain values ranging from 0.63 to 0.64, indicating medium gains. Students demonstrated enhanced abilities in observing, classifying, measuring, inferring, predicting, and communicating scientific concepts. The integrated approach facilitated practical application of knowledge, as evidenced by students' work on flood-resistant garage prototypes and wave-powered electricity generators. Qualitative findings revealed increased student engagement and improved problem-solving skills. The study concludes that the integration of the 9E Learning Cycle Model with STEM approaches offers an effective framework for enhancing students' science process skills and their ability to apply these skills to real-world problems. These recommendations aim to provide a more comprehensive understanding of the approach's potential in science education across various domains and student populations